2018 Vegetable Production Handbook Chapter 7: Cucurbit Production - Josh H. Freeman; Eugene J. McAvoy; Nathan S. Boyd; Monica Ozores-Hampton; Mathews Paret; Qingren Wang; Christian F. Miller; Johan Desaeger; Joseph W. Noling; Xavier Martini (EDIS)
This 28-page fact sheet is chapter 7 of the 2018 Vegetable Production Handbook. Written by Josh H. Freeman, Eugene J. McAvoy, Nathan S. Boyd, Monica Ozores-Hampton, Mathews Paret, Qingren Wang, Christian F. Miller, Johan Desaeger, Joseph W. Noling, and Xavier Martini, and published by the Horticultural Sciences Department, 2018.